Topographic heterogeneity triggers complementary cascades that enhance ecosystem multifunctionality - Tom P. Fairchild; Bettina Walter; Joshua J. Mutter; John N. Griffin (Ecology, 2024)
Topographic heterogeneity sets the stage for community assembly, but its effects on ecosystem functioning remain poorly understood. Here, we test the hypothesis that topographic heterogeneity underpins multiple cascading species interactions and functional pathways that indirectly control multifunctionality. To do so, we combined experimental manipulation of a form of topographic heterogeneity on rocky shores (holes of various sizes) with a comprehensive assessment of naturally assembled communities and multifunctionality. Structural equation modeling indicated that heterogeneity: (1) enhanced biodiversity by supporting filter feeder richness; (2) triggered a facilitation cascade via reef‐forming (polychaete) and biomass‐dominant (macroalga) foundation species, which in turn broadly supported functionally diverse epibiotic and understory assemblages; and (3) inhibited a key consumer (limpet). The model supported that these mechanisms exerted complementary positive effects on individual functions (e.g., water filtration, ecosystem metabolism, nutrient uptake) and, in turn, collectively enhanced multifunctionality. Topographic heterogeneity may therefore serve as a cornerstone physical attribute by initiating multiple cascades that propagate through ecological communities via foundation species, ultimately manifesting disproportionate effects on ecosystem multifunctionality.

Integrated assessment of climate change impacts on crop productivity and income of commercial maize farms in northeast South Africa - Davide Cammarano; Roberto O. Valdivia; Yacob G. Beletse; Wiltrud Durand; Olivier Crespo; Weldemichael A. Tesfuhuney; Matthew R. Jones; Sue Walker; Thembeka N. Mpuisang; Charles Nhemachena; Alex C. Ruane; Carolyn Mutter; et al. (Food Security, 2020)

A contemporary review of male breast cancer: current evidence and unanswered questions - Roberto A. Leon-Ferre; Karthik V. Giridhar; Tina J. Hieken; Robert W. Mutter; Fergus J. Couch; Rafael E. Jimenez; John R. Hawse; Judy C. Boughey; Kathryn J. Ruddy (Cancer and Metastasis Reviews, 2018)

Recent Advances in Multichannel Seismic Imaging for Academic Research in Deep Oceanic Environments - Juan Pablo Canales; Hélène Carton; John Mutter; Alistair Harding; Suzanne Carbotte; Mladen Nedimović (Oceanography, 2012)

Recent Seismic Studies at the East Pacific Rise 8°20'–10°10'N and Endeavour Segment: Insights into Mid-Ocean Ridge Hydrothermal and Magmatic Processes - Suzanne Carbotte; Juan Pablo Canales; Mladen Nedimović; Hélène Carton; John Mutter (Oceanography, 2012)

An Experiment in Institutional Transformation: The NSF ADVANCE Program for Women at the Earth Institute at Columbia University - Robin Bell; Jennifer Laird; Stephanie Pfirman; John Mutter; Roberta Balstad; Mark Cane (Oceanography, 2005)